Dual use satellites in the Ukraine conflict: The dilemma between state sovereignty and the principle of non-militarization of outer space - Muthia, Nuriyah Fara; Muhni, Afif; H., Nurisnah (Priviet Social Sciences Journal, 2025)
The increasing reliance on commercial satellite networks during armed conflicts has revealed substantial deficiencies in international space law. The Russia–Ukraine conflict serves as a pivotal case study, wherein Ukraine's utilization of SpaceX's Starlink satellite constellation for military communications obscured the distinction between civilian and military objects. This dual-use characteristic poses challenges to the traditional principles of international law, including state sovereignty over airspace, as delineated by the 1944 Chicago Convention, the freedom of outer space, as established by the 1967 Outer Space Treaty, and the principle of distinction under international humanitarian law. This study employs doctrinal legal analysis to assess whether dual-use satellites should be deemed legitimate military targets and to what extent states are accountable for the actions of private space actors. It contends that existing frameworks inadequately address the militarization risks posed by commercial satellites in low Earth orbit. The study concludes that new normative measures – whether through treaty amendments, interpretive declarations, or soft law instruments – are urgently needed to reconcile the competing principles of state sovereignty, civilian protection, and non-militarization of outer space.